Some Aspects of Chicken Behavior and Welfare - Costa, L. S. [UNESP]; Pereira, D. F. [UNESP]; Bueno, L. G. F. [UNESP]; Pandorfi, H. (Facta-fundacio Arnco Ciencia Tecnologia Avicolas, 2012)
Brazil is the world leader in broiler production and export. It achieved this position mainly to its excellent supply chain structure and climate, which favor poultry and grain production throughout its territory. Although Brazilian egg production is not as important as broiler production, this segment presents great potential of increasing its share in the global market. However, as elsewhere in the world, Brazilian poultry production faces the challenge to balance two elements within its supply chain: cruelty and productivity. The consumers of the European Union (EU) are very concerned with animal welfare issues. In order to increase its share in the European market, and eventually in the world market, Brazilian poultry producers must understand the effects of production systems on poultry welfare, and try to develop systems that are suited for its climate and other production conditions. There is a consensus that the natural behaviors performed by poultry in intensive production systems allow better welfare. This objective of this review is to present scientific research studies that relate different behaviors to chicken welfare. Poultry behavior is a reflex of their welfare status at a particular moment, and it is related to internal (physiological) and external (environmental) factors. Several natural behaviors that favor welfare, as well as undesirable behaviors, may be stimulated by environmental enrichment. The correct interpretation of the behaviors expressed by poultry, including their frequency, duration, and sequence, may be used to estimate their welfare. Animal production is an import sector of Brazilian economy. It significantly contributes to the Gross Domestic Product (GDP), in terms of products destined both to domestic consumption and exports. New technologies applied to products and management practices have been developed for field application, aiming at improving producers' productivity and profitability. In order to comply with the European Union's (EU) guidelines for animal protein production, Brazilian poultry production needs to undergo a process of adaptation. In May, 2007, the EU Commission established its new guidelines for animal welfare in poultry production, pressured by consumer demand. In the EU, there is a growing concern among consumers as to how poultry are reared and slaughtered. European consumers are in the fore front of the demand of high quality products produced with under better welfare conditions, and have spread this concern throughout the world. Beaumont et al. (2010) mentioned that European consumers frequently perceive that standard commercial poultry production has poor animal welfare practices. According to Naas et al. (2008), Brazilian poultry production today needs to find a balance between cruelty and productivity. In fact, ensuring animal welfare may provide better financial results, as it increases the producer's profit margins and allows maintaining Brazilian chicken export quotas to the EU. Franca (2008) noted that biological studies that define ethical limits and guidelines for poultry production foster the development of new production practices that may ensure good product quality and productivity without putting bird welfare at risk. Gonyou (1994) states that, when animal welfare started to be studied, the only behavioral factors considered were those related to feeding and reproduction. These first studies used as indicators of animal welfare reduced life expectancy, impaired growth, impaired reproduction, body damage, disease, immunosuppression, adrenal activity, behavior anomalies, and self-narcotization (Broom, 1991). However, current studies evaluate additional indicators, such as natural behaviors, behavioral needs, preferences, behavioral problems, emotional state, cognitive abilities, etc. In the field of ethology, the expression of natural behavior is a frequently used tool used to estimate the welfare of poultry destined to human consumption. According to Bracke & Hopster (2006), natural behavior can be defined as the behavior the animal normally presents when exposed to conditions similar to its natural habitat. Natural behaviors are pleasurable and promote biological functions that are meaningful to the animal's welfare. The definition of natural behavior, though, does not include the bird's behavior when sick, in flight or during aggression, since these are not considered pleasurable situations. Considering layer behavioral needs in the design of housing facilities optimize their welfare. Mishra et al. (2005) verified that ISA Brown layers spent, during 24 hours, around 97% of the time in the nest, feeding, walking, resting, or dust bathing, and that 57% of these behaviors did not depend on environmental enrichment. It was also observed that hens had preferred behavioral sequences, which included foraging and comfort behaviors, such as wing-stretching and preening. The present review aims at discussing, albeit not exhaustively, scientific research studies on the behavior of Gallusgallus domesticus and its relationship to welfare. The following behaviors are reviewed: feather pecking, scratching, dust bathing, nesting, locomotion activities, and aggressive behaviors. These behaviors are the most frequently observed in commercial broiler, broiler breeder, and layer farming, and therefore, monitoring their incidence may contribute to measure poultry welfare.
Keywords: Enriched environment; precision poultry production; consumer market; productivity